4.3 Laws of Logarithms

download 4.3 Laws of Logarithms

of 9

  • date post

    17-Jan-2016
  • Category

    Documents

  • view

    47
  • download

    3

Embed Size (px)

description

4.3 Laws of Logarithms. Laws of Logarithms. Just like the rules for exponents there are corresponding rules for logs that allow you to rewrite the log of a product , the log of a quotient , or the log of a power. Log of a Product. Logs are just exponents - PowerPoint PPT Presentation

Transcript of 4.3 Laws of Logarithms

  • 4.3 Laws of Logarithms

  • *Laws of Logarithms Just like the rules for exponents there are corresponding rules for logs that allow you to rewrite the log of a product, the log of a quotient, or the log of a power.

  • *Log of a ProductLogs are just exponentsThe log of a product is the sum of the logs of the factors:logb xy = logb x + logb yEx: log (25 125) = log 25 + log 125

  • *Log of a QuotientLogs are exponents The log of a quotient is the difference of the logs of the factors: logb = logb x logb y Ex: ln ( ) = ln 125 ln 25

  • *Log of a PowerLogs are exponents The log of a power is the product of the exponent and the log: logb xn = nlogb x Ex: log 32 = 2 log 3

  • *Rules for Logarithms These same laws can be used to turn an expression into a single log: logb x + logb y = logb xy logb x logb y = logb nlogb x = logb xn

  • *logb(xy) = logb x + logb yExpressas a sum and difference of logarithms:= log3A + log3BExampleslogb( ) = logb x logb ylogb xn = n logb x_______________________________Solve: x = log330 log310 = log33Evaluate: = 2 = log3Cx = 1= log3 AB

  • *Sample Problem Express as a single logarithm:3log7x + log7(x+1) - 2log7(x+2) 3log7x = log7x3 2log7(x+2) = log7(x+2)2log7x3 + log7(x+1) - log7(x+2)2 log7(x3(x+1)) - log7(x+2)2

    log7(x3(x+1)) - log7(x+2)2 =

  • To use a calculator to evaluate logarithms with other bases, you can change the base to 10 or e by using either of the following:For all positive numbers a, b, and x, where a 1 and b 1:Example: Evaluate log4 22

    2.2295Change of Base Formula

    *